2020
DOI: 10.47743/saeb-2020-0021
|View full text |Cite
|
Sign up to set email alerts
|

Higher Education Funding and Economic Growth: Empirical Evidence from Croatia

Abstract: Deprived of investment in education, no country can expect sustainable economic growth and development. Higher education is particularly a priceless tool in today's era of globalization that requires continuous education to keep up with new knowledge. According to UNESCO (2014), higher education is no longer a luxury; it is essential to national, social and economic development. The impact of education on economic growth is possible to observe within the so-called ‘education led growth hypothesis’. The main ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…Consequently, social welfare, here, is specified as a function which positively depend on human capital and inclusion, while negatively on factors such as education's cost and exclusion (e.g., admission rationing). In reality, this specification is supported by several empirical studies (on this see for example, Morley et al, 2009;Dearden et al, 2011;Caner and Okten, 2013;Radic and Paleka, 2020), which show that raising human capital in the society leads to more economic growth and welfare, whereas raising costs, and imposition of other obstacles to education's access, contribute towards deepening inequalities, and thus undermining social welfare. More formally, Lemma 1 Social welfare is a function which increases in human capital, and decreases in tuition fee and admission criteria…”
Section: Social Welfarementioning
confidence: 86%
“…Consequently, social welfare, here, is specified as a function which positively depend on human capital and inclusion, while negatively on factors such as education's cost and exclusion (e.g., admission rationing). In reality, this specification is supported by several empirical studies (on this see for example, Morley et al, 2009;Dearden et al, 2011;Caner and Okten, 2013;Radic and Paleka, 2020), which show that raising human capital in the society leads to more economic growth and welfare, whereas raising costs, and imposition of other obstacles to education's access, contribute towards deepening inequalities, and thus undermining social welfare. More formally, Lemma 1 Social welfare is a function which increases in human capital, and decreases in tuition fee and admission criteria…”
Section: Social Welfarementioning
confidence: 86%
“…In turn, Jovović et al [22], in a study conducted on the labor market in Montenegro, concluded that the inadvertencies between the needs of the educational system and the needs of the labor market can significantly influence economic growth and economic development. Another paper, which analyzed the effects of the financing of education in Croatia using "the hypothesis of growth driven by education", tested the fact that Croatia could flourish following increased financing of higher education [23]. At the same time, another analysis confirmed the existence of a positive impact of vocational training costs on economic growth, allowing the authors to conclude that there was a need to develop professional training programs for staff as one of the drivers of macroeconomic development [24].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Tsamadias and Prontzas (2012) show for Greece that education has a positive and statistically significant impact on economic growth, while Granger causality results reveal evidence of unidirectional long-term and short-term causality from higher education to economic growth. Radić and Paleka (2020) reveal a unidirectional causality from higher education expenditure to economic growth in the short-run in Croatia. Popović et al (2019) indicate that education affects economic development positively in Bosnia and Herzegovina.…”
Section: A Brief Literature Survey: the Mediterranean Casementioning
confidence: 99%